The Influence of Leadership Style and Custome Satisfaction on Employee Performance Through Work Motivation Mediation at PT Ume Persada Indonesia - Chusnul Chakim; Djoko Soelistya (LP2M IAIN Palopo, 2024)
There is a novelty through the mediation of work motivation which is expected to help improve employee performance and most. And it can be seen that previous researchers used the variable of work motivation as a variable that directly influences leadership style and customer satisfaction. The approach used in this study is a quantitative approach. the results of the analysis that have been described Leadership Style has an influence on Employee Performance. Customer Satisfaction has an influence on Employee Performance Leadership Style has an influence on Work Motivation customer Satisfaction has an influence on Work Motivation Work Motivation has an influence on Employee Performance Leadership Style has an influence on Employee Performance through Work Motivation as a partial mediation Customer Satisfaction has an influence on Employee Performance through Work Motivation as a partial mediation.